LEGAL PROTECTION OF CONSUMER OWNER OF FLAT ON WITHDRAWAL OF ENVIRONMENTAL MANAGEMENT CONTRIBUTIONS (IPL) ACCORDING TO GOVERNOR REGULATION NO. 133 OF 2019 - Bantolo, Arief Setyo; Ismail; Ismet, Mohamad (Transpublika Publisher, 2022)
This paper discusses the legal protection of consumers of apartment owners for the withdrawal of environmental management fees (IPL) in accordance with Governor Regulation No. 133 of 2019. The approach method used in this legal research is a normative juridical approach which is supported by empirical juridical by detailing the description, namely a research that begins deductively analyzing the articles in the legislation. The construction of flats in Indonesia is based on Law Number 20 of 2011 concerning Flats, the law also requires that if the apartment unit already has occupants or has been occupied, it is required to form an association of flat occupants. This obligation must be carried out by the occupants and by the development organizer, which means that every construction of a flat unit is required to form an Association of Residents of Flats (P3SRS) which is a legal entity. The researcher found the problem that the need for legal protection for residents of apartment units in the field of apartment management, there is a shopping center that was established based on Law Number 20 of 2011 concerning Flats in the form of flats, and the Governor Regulation No. 133 of 2019 which has been established for a long time and formed an apartment unit, but has not yet formed an association that is a legal entity.